A dinâmica dos gastos com saúde e educaç\~ao públicas no Brasil (2006-2015): Impacto dos mínimos constitucionais e relaç\~ao com a arrecadaç\~ao tributária - Cláudio H. dos Santos; Bernardo Patta Schettini; Lucas Ferraz Vasconcelos; Érica Lima Ambrosio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text aims to offer three contributions to the study of Brazilian public expenditures on health and education. First by constructing annual and bimonthly estimates of these expenditures in order to allow time series analyses of their historical evolution. Second by analysing the relative importance of the constitutional constraints affecting these expenditures during the year covered in this research. Third by analysing the relationship between the dynamics of these expenditures and of tax revenues. The results reported in this text suggest that the constitutional constraints are binding for several Brazilian states and thousands of Brazilian municipalities. They sugggest also that Brazilian public expenditures on health and education are both cointegrated with tax revenues.
Keywords: H51; H52; H75; I18; I28; 330; public expenditure on health; public expenditure on education; constitutional earmarking of tax revenues